2006
DOI: 10.1177/0170840606065701
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic Decision Making and Organizations: Reviewing Pragmatic Science

Abstract: highlighting an area where these two pragmatic research paradigms overlap. Not only do researchers in these areas aim to improve our understanding of decision making, they provide practical and realistic alternatives to laboratory-based research on decision making. The article presents a number of propositions for future research on NDM and organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 51 publications
0
54
0
Order By: Relevance
“…information, scenario detail) leading to this decision; ○ Influence of organisational factors (e.g. protocols, norms) underlying decision-making; (Bertsimas, Farias, and Trichakis 2012;Pauker and Kassirer 1975), framing effects upon decision-making (Croskerry 2002;Fackler et al 2009;Kahneman, Slovic, and Tversky 1982), experience and expertise (Flin, Youngson, and Yule 2007;Klein 1993;Patel, Kaufman, and Arocha 2002), and organisational and group norms for decision-making (Eisenberg 1979;Gore et al 2006). Finally, the themes and data from the qualitative analysis were summarised and synthesised into a single table, which aimed to provide an initial conceptual set (illustrated by examples) of factors influencing how clinicians make risk trade-offs in ICU.…”
Section: Interview Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…information, scenario detail) leading to this decision; ○ Influence of organisational factors (e.g. protocols, norms) underlying decision-making; (Bertsimas, Farias, and Trichakis 2012;Pauker and Kassirer 1975), framing effects upon decision-making (Croskerry 2002;Fackler et al 2009;Kahneman, Slovic, and Tversky 1982), experience and expertise (Flin, Youngson, and Yule 2007;Klein 1993;Patel, Kaufman, and Arocha 2002), and organisational and group norms for decision-making (Eisenberg 1979;Gore et al 2006). Finally, the themes and data from the qualitative analysis were summarised and synthesised into a single table, which aimed to provide an initial conceptual set (illustrated by examples) of factors influencing how clinicians make risk trade-offs in ICU.…”
Section: Interview Protocolmentioning
confidence: 99%
“…Organisational and social psychology research shows that decision-making on risk is often influenced by social norms for how risk is understood and responded to (Bettenhausen and Murnighan 1985;Gore et al 2006;Trevino 1986). This appeared relevant for both scenarios.…”
Section: Organisational and Group Normsmentioning
confidence: 99%
“…Overall, these factors include: ill-structured problems; uncertain dynamic settings; Shifting and competing goals; action/feedback loops; time pressure; high stakes; multiple decision makers; and organizational goals and norms; and experienced decision-makers [20][21][22]. The worst cases for decision makers are the ones with maximum values on the eight features mentioned above.…”
Section: Naturalistic Decision Making (Ndm)mentioning
confidence: 99%
“…fields such as nuclear power, aviation, healthcare (Gore, Banks et al, 2006) and intelligence analysis (Hutchins, Pirolli et al, 2004). It was used primarily to identify perceptual and cognitive needs for aiding decision making, and to investigate incidents by reconstructing and understanding how operators made sense of the emergent situations (Klein, 2008).…”
Section: History Of the Methodsmentioning
confidence: 99%
“…It has its beginnings in the rejection of Subjective Expected Utility theory where people are thought to make decisions by analysing all possible outcomes of a situation in a very rationalistic manner and selecting the most desirable option (Gore, Banks et al, 2006). Early researchers in NDM, including Gary Klein, found that in real situations people generated a very limited number of possible courses of action, sometimes only one, and then compared them to the constraints of the situation for a reason to reject the course of action (Klein, 2008).…”
Section: 1 Naturalistic Decision Makingmentioning
confidence: 99%